2023
DOI: 10.3390/nano13081322
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automated and High-Throughput Quantitative Sizing and Isotopic Analysis of Nanoparticles via Single Particle-ICP-TOF-MS

Abstract: The work described herein assesses the ability to characterize gold nanoparticles (Au NPs) of 50 and 100 nm, as well as 60 nm silver shelled gold core nanospheres (Au/Ag NPs), for their mass, respective size, and isotopic composition in an automated and unattended fashion. Here, an innovative autosampler was employed to mix and transport the blanks, standards, and samples into a high-efficiency single particle (SP) introduction system for subsequent analysis by inductively coupled plasma–time of flight–mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…61 In a different study, the robustness and reproducibility of this autosampler was successfully demonstrated for nanoparticles analysis and holds great promises for high-throughput single-cell analysis. 62…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 In a different study, the robustness and reproducibility of this autosampler was successfully demonstrated for nanoparticles analysis and holds great promises for high-throughput single-cell analysis. 62…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, this facilitated assessment of the method, but we would envision that one would also be able to measure lower concentrations of nanoplastics (and their association with cells) should exposure concentrations be reduced. Furthermore, the strength of the method relies on its adaptability and its potential for automation through use of an autosampler allowing for unattended operation 62 and automated data processing, which together allow for the analysis of more cells and would facilitate capturing more infrequent nanoplastics/cells associations at reduced exposure concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…An icpTOF R (TOFWERK AG, Thun, Switzerland) was integrated with a microFAST SC sample introduction system from Elemental Scientific Inc (ESI, Omaha, NE, USA) for high throughput analysis. 29 The operating conditions of the ICP-TOF-MS can be found in Table 1. The ICP-TOF-MS was operated in collision cell technology (CCT) mode using ultra high purity (99.999%) H 2 and He gases (Airgas, Radnor, Pa, USA) to remove ArO interferences at m / z 56 and 57.…”
Section: Methodsmentioning
confidence: 99%
“…The microFAST SC autosampler sequence was created as described previously 29 in a study characterizing nanoparticles. Briefly, the autosampler probe goes into the sample and mixes via high speed (3000 μL min −1 ) alternating pumping of the sample using a syringe pump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation